PERAN KH SOMALANGU DALAM GERAKAN ANGKATAN UMAT ISLAM DI KEBUMEN TAHUN 1945-1950 - Intan Dwi Anggraeni; Darsono Darsono (KARMAWIBANGGA: Historical Studies Journal, 2022)
This study aims to: (1) describe the general condition of Kebumen around the proclamation of Indonesian independence; (2) describe the biography of KH Somalangu; (3) describe the role of KH Somalangu in the Movement of the Muslims of 1945-1950 in KebumenThis study uses literature review method. Data collection is done by collecting written sources that can be found in books, journals, thesis and the internet. The steps in this study are heuristics, source criticism or verification, interpretation, and historiography.The results of this study are: (1) Kebumen which is included in the residency of Kedu with the livelihood of the population is farming and the majority are Muslim; (2) KH Somalangu had the birth name of Syeikh As_Sayid Mahfudz Al-Hasani or Syeikh Mahfudz Abdurrahman who was born in Kebumen on November 9, 1901; (3) The role of KH Somalangu is divided into three periods, namely AUI during Military Aggression 1, AUI during Military Aggression 2, and AUI during rebellion.Â